Medical devices modified at the surface by gamma-ray grafting for drug loading and delivery - Alvarez-Lorenzo, Carmen; Bucio, Emilio; Burillo, Guillermina; Concheiro, Angel (Expert opinion on drug delivery, 2010)
Medical devices with the capability of hosting drugs are being sought for prophylaxis and treatment of inflammatory response and microbial colonization and proliferation that are associated with their use. This review analyzes the interest of gamma-ray irradiation for providing medical devices with surfaces able to load drugs and to deliver them in a controlled way. The papers published in the last 20 years on the subject of gamma-ray irradiation methods for surface functionalization of polymers and their application for developing medicated medical devices are discussed. The information reported may help to gain insight to the state-of-the-art of gamma-ray irradiation approaches and their current advantages/limitations for tailoring the surface of medical devices to fit preventive and curative demands. Grafting of polymer chains able to establish specific interactions with the drug, grafting of stimuli-responsive networks that regulate drug diffusion through the hydrogel-type surface as a function of the surrounding conditions, and grafting of cyclodextrins that control uptake and delivery through the affinity constant of inclusion complexes have been revealed as efficient approaches for endowing medical devices with the capability of also acting as drug delivery systems.